Management of Quality Chemistry Science Laboratories in School - Saitong, Sutasinee; Sakulsriprasert, Suphattra (Journal for Developing the Social and Community, 2026)
Background and Aims: The effective management of chemistry laboratories in educational institutions is a crucial process that supports practical learning, enhances students’ analytical thinking and experimental skills, and ensures systematic operations with safety standards and efficient use of resources. This is essential to achieve optimal learning outcomes while ensuring safety for all stakeholders. The objectives of this research are: (1) to study and analyze the current conditions and developmental needs of chemistry laboratory management plans, and (2) to develop and validate guidelines for effective management of quality chemistry laboratories in educational institutions. Methodology: This research is a qualitative study conducted in three phases: Phase 1 involved analyzing the developmental needs of chemistry laboratory management; Phase 2 focused on developing guidelines for quality management of chemistry laboratories in educational institutions; and Phase 3 examined the validity of the proposed management guidelines. The sample consisted of one school administrator, two academic teachers, five science teachers, one chemistry laboratory supervisor, and one school board member. The research instruments included expert-based discussion records, workshop agendas and minutes, as well as a checklist for verifying the validity and feasibility of the chemistry laboratory management guidelines. Quantitative data analysis was conducted using percentage analysis, while qualitative data were analyzed through content analysis. Results: 1) The study of current conditions and developmental needs for establishing guidelines in managing chemistry laboratories in schools revealed three key aspects: Physical aspect: Insufficient equipment and space, which negatively affect instructional efficiency. Social aspect: Lack of communication and collaboration between teachers and laboratory staff. Educational aspect: The curriculum does not sufficiently emphasize microscale chemistry techniques, and training on laboratory safety is limited. The developmental needs identified include establishing clear guidelines for resource management, ensuring safe use of equipment, implementing environmentally friendly chemical management systems, and integrating microscale chemistry techniques into the curriculum to promote safe and effective learning. 2) The development of management guidelines for quality chemistry laboratories in educational institutions was structured around four areas: (1) Laboratory management measures ensuring adequate, safe, and learning-conducive spaces and resources, while integrating microscale chemistry techniques and green chemistry concepts. (2) Management processes based on POSDCoRB principles to enhance efficiency and sustainability in laboratory operations. (3) Prudent resource management covering equipment, chemicals, safety systems, and budgeting. (4) Stakeholder engagement encouraging administrators, teachers, staff, and students to collaborate in creating a safe and high-quality learning environment. Expert evaluations of the guidelines indicated the highest level of validity (𝑥̅ = 4.92, S.D. = 0.28) and feasibility (𝑥̅ = 4.88, S.D. = 0.32). Conclusion: The management of chemistry laboratories in educational institutions still faces limitations in terms of equipment, personnel, and curriculum. The developed guidelines emphasize safe and efficient resource management. Integrating microscale chemistry techniques and green chemistry concepts promotes safe, environmentally friendly learning. The guidelines cover laboratory administration, resource management processes, and the roles of all stakeholders. Evaluation results indicate that the guidelines are both valid and practically applicable in schools.